An indispensable truth how fusion power can save the planet - Chen, Francis F. 1929-; SpringerLink (Online service). (New York Dordrecht Springer, 2011)
Both global warming and oil shortage can be solved by controlled fusion, a clean power source that will serve mankind for millennia. The idea of hydrogen fusion as well as its difficulties are presented in non-technical language to dispel the notion that fusion is always 50 years away.? This book also summarizes the evidence for climate change and explains the principles of both fossil and "green" energy sources to show that fusion is the best alternative for central-station power in the near term as well as the far future. Praise for An Indispensable Truth: How Fusion Power Can Save the Planet: "In this study Professor Chen outlines the underlying physics, recent progress in achieving advanced plasmas and magnetic confinement, and hopes for the future. He recognizes the difficulties that remain in engineering a fusion reactor, but he remains optimistic regarding ultimate success, yet fearful of the consequences were we to fail."- James R. Schlesinger, former Chairman, Atomic Energy Commission; Director, Central Intelligence Agency; Secretary of Defense; and Secretary of Energy "With lots of detail and examples, Chen brings the technical topic of fusion to life, making the book a great read for scientists and nonscientists alike."- Representative Rush Holt (D-NJ) "Professor Chen has opened the door to energy survival for our globe. His insightful analysis makes the case for fusion energy, and he conveys both its complexity and its promise. This book is a must for all those who are concerned about the energy future of our species."- Raymond L Orbach, former Undersecretary for Science, U.S. Department of Energy "This is an important book for anyone who wishes to understand the greatest challenge we face. Frank Chen makes the science of fusion and energy clear, compelling, and hugely enjoyable."- Steven Cowley, Director and CEO, Culham Centre for Fusion Energy, United Kingdom Atomic Energy Authority.
Preface -- Prologue -- The Evidence for Climate Change -- The Future of Energy I:  Fossil Fuels -- The Future of Energy II:  Renewable Energy -- Fusion:  Energy from the Seawater -- Perfecting the Magnetic Bottle -- The Remarkable Tokamak -- Evolution and Physics of the Tokamak -- A Half-century of Progress -- Engineering:  The Big Challenge -- Fusion Concepts for the Future -- Conclusions -- Epilogue.
Electronic reproduction.
Keywords: Controlled fusion; Direct energy conversion; Fusion reactors; Plasma (Ionized gases); Renewable energy sources; Global warming -- Research; Electronic books